Estimating access to surgical care: A community centered national household survey from Pakistan. - Muhammad Nabeel Ashraf; Irum Fatima; Ammar Ali Muhammad; Katherine Albutt; Manon Pigeolet; Asad Latif; John G Meara; Lubna Samad (Public Library of Science (PLoS), 2023)
Pakistan is a lower middle-income country in South Asia with a population of 225 million. No estimate for surgical care access exists for the country. We postulate the estimated access to surgical care is less than the minimum 80% to be achieved by 2030. We conducted a randomized, stratified two-stage cluster household survey. A sample of 770 households was selected using 2017 census frames from the Pakistan Bureau of Statistics. Data was collected on choice of hospital and travel time to the chosen hospital for C-section, laparotomy, open fracture repair (OFR), and specialized surgery. Analysis was conducted using Stata 14. Access to all Bellwether surgeries (C-section, laparotomy, and open fracture repair) in Pakistan is estimated to be 74.8%. However, estimated access in rural areas and the provinces of Balochistan, Khyber Pakhtunkhwa (KP) and Sindh is far less than in urban areas and in Punjab and Islamabad. Estimated access to C-sections is more compared to OFR, laparotomy, and specialized surgery. Health system strengthening efforts should focus on improving surgical care access in rural areas and in Balochistan, KP, and Sindh. More focus is required on standardizing the availability and quality of surgical services in secondary-level hospitals.